2022
DOI: 10.21203/rs.3.rs-2191270/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measured and perceived effects of audit and feedback on nursing performance: A mixed methods systematic review

Abstract: Background: The use of audit and feedback in health care has been shown to have generally positive effects with medical teams, but little is known about its effects on nursing care. The purpose of this systematic review was to examine the evidence of measured and perceived effects of such interventions on nursing performance. Methods: We used a mixed-methods systematic review design with thematic and narrative synthesis. Studies reporting quantitative and qualitative data on the effects of feedback interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The findings in this article are based on an analysis of empirical data from a mixed-methods systematic review of the literature 9 and on the findings from a pilot study on the design and testing of an A&F intervention with a nursing team in primary care. 10 The review includes data from quantitative (n = 13) and qualitative (n = 18) studies that reported effects of A&F interventions conducted with nurses between 1995 and 2021.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings in this article are based on an analysis of empirical data from a mixed-methods systematic review of the literature 9 and on the findings from a pilot study on the design and testing of an A&F intervention with a nursing team in primary care. 10 The review includes data from quantitative (n = 13) and qualitative (n = 18) studies that reported effects of A&F interventions conducted with nurses between 1995 and 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Data on the process and outcome indicators related to wound care episodes were reported to the team. Full details of the methods used are described in the articles reporting the results of the review 9 and the pilot study. 10 By synthesizing quantitative and qualitative data from empirical studies, researchers identified patterns in nurses' responses to A&F interventions in different contexts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations